Global Economic Growth and Environmental Change - Wei-Bin Zhang (SPOUDAI - Journal of Economics and Business, 2014)
The purpose of this paper is to examine dynamic interdependence between wealth accumulation, capital accumulation, economic structure, domestic and global division of labor, international trade and environmental change with transboundary pollution. It analyzes not only inequalities in income, wealth and economic structures between (any number of) countries, but also differences in environmental changes between countries. The model is built on the basis of the Solow model, the Uzawa two-sector growth model, the Oniki-Uzawa trade model, and the neoclassical growth models in environmental economics. The general equilibrium dynamic model includes any number of national economies and each national economy has two sectors. After building the model, we show that the dynamics of the world economy with countries is described by differential equations. We simulate the motion of the global economy with three national economies. We also examine the effects of changes in the propensity to environmental taxes, the efficiency of environmental protection, and the population upon dynamic paths of the system. Our analysis provides some insights into the complexity of global economic growth with environment. For instance, the well-known study by Grossman and Krueger (1995) identifies no evidence that "environmental quality deteriorates steadily with economic growth." Our simulation indicates that this conclusion holds for some countries, but is invalid for other countries.
Keywords: F11; O41; Q56; 330; trade; economic growth; transboundary pollution; environmental change; environmental policies